Lagu sebagai Cermin Psikologis Generasi Muda: Studi Kesehatan Mental dalam Karya Musik Hindia : Penelitian - Syaharani Astuti; Khodijah Dra (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Finding out how Hindia songs might shed light on Indonesian youths' psychological states, particularly those pertaining to mental health, was the aim of this study. This study involved Gen Z respondents who actively listen to Hindia music using a quantitative technique based on a Google Forms poll. According to the survey's findings, the majority of participants said Hindia songs might help them comprehend and express their emotions as well as accurately describe them. Approximately 93.33% of respondents stated that they frequently listened to Hindia songs, and 83.33% thought the songs could accurately depict the mental health of the younger generation. This suggests a sentimental and symbolic connection between performers and their audience. Furthermore, around 70% of those surveyed thought that music helped people communicate their psychological problems. This finding is supported by neuropsychological research, which demonstrates that music listening can influence dopamine, prolactin, and cortisol production all of which have an effect on emotional regulation. Additionally, music can enhance communication between brain regions including the prefrontal cortex and nucleus accumbens and decrease amygdala activity, which contributes to anxiety. This shows that music, especially Hindia songs, may be both a source of amusement and a useful tool for enhancing teenagers' comprehension of mental health concerns. Thus, it's critical to keep studying how music might enhance psychological health and lessen the stigma attached to mental health in Indonesian youth.